PENGARUH PELAYANAN PERPUSTAKAAN TERHADAP MINAT BACA SISWA SD - Ardiansyah Ardiansyah (Universitas Wijaya Kusuma Surabaya, 2020)
This study aims to determine the effect of library services on elementary school students 'reading interest and how its significance. This research method uses quantitative methods with the